2013
DOI: 10.1039/c3cs35480f
|View full text |Cite
|
Sign up to set email alerts
|

Nano-magnetite (Fe3O4) as a support for recyclable catalysts in the development of sustainable methodologies

Abstract: Surface functionalization of nano-magnetic nanoparticles is a well-designed way to bridge the gap between heterogeneous and homogeneous catalysis. The introduction of magnetic nanoparticles (MNPs) in a variety of solid matrices allows the combination of well-known procedures for catalyst heterogenization with techniques for magnetic separation. Magnetite is a well-known material, also known as ferrite (Fe3O4), and can be used as a versatile support for functionalization of metals, organocatalysts, N-heterocycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
560
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,137 publications
(567 citation statements)
references
References 220 publications
2
560
0
5
Order By: Relevance
“…9 The surface functionalized NPs can be used to bridge the gap between heterogeneous and homogeneous catalysis. 10 Among different noble metals like Au, Ag, Pd, Pt, Cu, Ir, Rh, Ru and Os, the study on osmium metal NPs has found very limited application. Osmium is an interesting noble metal which competes with iridium and has very low compressibility, a high melting point and high bulk modulus.…”
Section: Introductionmentioning
confidence: 99%
“…9 The surface functionalized NPs can be used to bridge the gap between heterogeneous and homogeneous catalysis. 10 Among different noble metals like Au, Ag, Pd, Pt, Cu, Ir, Rh, Ru and Os, the study on osmium metal NPs has found very limited application. Osmium is an interesting noble metal which competes with iridium and has very low compressibility, a high melting point and high bulk modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Bare magnetic NPs have been successfully used as catalysts in some catalytic processes. They could also be protected with inorganic supports or directly decorated with transition-metal NPs [35]. In the latter usages, magnetic NPs have been extensively employed as alternative catalyst supports.…”
Section: Sustainable Magnetic Nanostructured Catalystsmentioning
confidence: 99%
“…Among many applications, superparamagnetic nanosystems can be used for magnetic data storage (Eigler et al 2014), polluting agent removal (Nethaji et al 2013), or, more recently as catalysts for organic reactions (Gawande et al 2013, Obermayer et al 2013. Beside these numerous applications, SPIONs are widely used nanomaterials for biomedical purposes, such as magnetic resonance imaging (MRI) , hyperthermia for cancer therapy (Jin et al 2008), cell targeting (Das et al 2008), drugs or gene delivery (Namvari and Namazi 2014).…”
Section: Introductionmentioning
confidence: 99%